Cape - Hannigan, Kate (Hannigan, Kate. League of Secret Heroes, 2019)
Soon after being recruited by the mysterious Mrs. Boudica to join a secret military intelligence operation, Josie, Mae, and Akiko discover their superhero abilities and use them to thwart a Nazi plot to steal the ENIAC computer.